Hydrosalpinx – Salpingostomy, salpingectomy or tubal occlusion. (August 2019) - Ng, Ka Ying Bonnie; Cheong, Ying
Abstract: Tubal factors account for approximately 25% of cases of infertility, and the most severe manifestation of tubal disease is hydrosalpinx, accounting for 10–30% of tubal diseases. Hydrosalpinx is a distension or dilatation of the fallopian tube in the presence of a distal tubal occlusion, and the most common cause is pelvic inflammatory disease. Women with hydrosalpinges have lower implantation and pregnancy rates in assisted reproductive technology (ART), due to a combination of mechanical and chemical factors thought to disrupt the endometrial environment. Current guidance is removal of the tube by salpingectomy (preferably laparoscopically) before IVF treatment. Salpingostomy, or distal tubal plastic surgery in the management of hydrosalpinx, is an alternative for women desiring natural conception, although ectopic pregnancy rates as high as 10% have been reported. Proximal tubal occlusion with Essure ® devices placed hysteroscopically can be considered particularly in cases of distorted pelvic anatomy or pelvic adhesions making abdominal surgery complex. However, low clinical pregnancy and live birth rates have been reported with the use of these devices before IVF. In this review, we discuss salpingostomy, salpingectomy and tubal occlusion as possible management options for the reproductive women with hydrosalpinx. Highlights: Hydrosalpinx is a distension of the fallopian tube in the presence of a distal tubal occlusion, and the most common cause is pelvic inflammatory disease. Women with hydrosalpinges have lower implantation and pregnancy rates in assisted reproductive technology. Current guidance is removal of the tube by salpingectomy (preferably laparoscopically) before IVF treatment. Salpingostomy, is an alternative for women desiring natural conception, although ectopic pregnancy rates as high as 10% have been reported. Tubal occlusion with Essure ® devices placed hysteroscopically can be considered; however, it results in low clinical pregnancy and live birth rates before IVF.